Helicobacter pylori-negative intestinal-type gastric adenoma successfully treated by endoscopic submucosal dissection: a case report - Kobayashi, Yoshiya; Komazawa, Yoshinori; Nagaoka, Makoto; Takahashi, Yoshiko; Yuki, Mika; Shizuki, Toshihiro; Nabika, Toru (Endoscopy International Open, 2016)
Background and study aims: A 49-year-old woman underwent an esophagogastroduodenoscopy as part of a health check at our hospital. Endoscopic observation revealed a flat elevated lesion 6 mm in diameter in the gastric antrum (Paris Classification type IIa). Magnifying endoscopy using narrow-band imaging showed a slightly irregular micro-surface pattern with round and oval pits, as well as a regular micro-vascular pattern without a demarcation line. Atrophy and intestinal metaplasia were not recognized in the background gastric mucosa. Furthermore, Helicobacter pylori infection was not detected by histologic, serologic, and urea breath test results. Endoscopic resection was performed for histologic evaluation, and a pathologic diagnosis of intestinal-type gastric adenoma occurring in pyloric mucosa without atrophy or metaplasia was established. Immunohistochemistry findings of the lesion showed the intestinal epithelium phenotype with positive staining for MUC2, CD10, and CDX2. Furthermore, irregular distribution with a higher positive proportion of Ki-67 was found in the lesion, indicating its malignant potential. We report here a rare case of gastric adenoma without surrounding intestinal metaplasia occurring in a Helicobacter pylori-negative patient.